The Effect of Workload and Psychological Capital on Burnout for Media Company Employees in Cirebon City, West Java, Indonesia - Setiawan, Tegar; Murtafiq, Ahmad (International Journal of Business, Economics, and Social Development, 2024)
This study aimed to determine how workload and psychological capital impact burnout among employees of media companies in Cirebon City. This study used the quantitative method to collect primary data by distributing Likert-scale questionnaires directly to 17 media companies around Cirebon City. Secondary data came from research methodology books and national and international official journals. The researcher conducted data analysis using SPSS to test the hypothesis and research model. Using the non-probability purposive sampling method, the research sample was 153, collected from 17 media companies. The results showed that workload has a positive and significant effect on burnout, psychological capital has a negative and significant effect on burnout, and workload and psychological capital have a significant relationship with burnout among employees of media companies in Cirebon City, West Java, Indonesia.